Development of NiFe2O4/Au nanoparticles covered with lipid bilayers for applications in combined cancer therapy - Rodrigues, Ana Rita Oliveira (2019)
The potential of nanosystems with combined magnetic and plasmonic properties for biomedical applications has been recognized. Magnetic nanoparticles can enable magnetic drug targeting and hyperthermia, while plasmonic gold nanoparticles ensure effective local heating (photothermia) using relatively low energies for gold excitation. Considering cancer therapy, the combination of magnetic and plasmonic capabilities in a single multifunctional nanosystem allows magnetic guidance and production of local heat, the latter promoting triggered drug release and synergistic cytotoxic effect in cancer cells (combined chemo/phototherapy). In order to develop applications in combined cancer therapy, magnetic/plasmonic nanoparticles were prepared and covered with a lipid bilayer, these systems being able to transport drugs. The photothermia capabilities of these nanosystems were evaluated.